2012
DOI: 10.5897/ajmr12.001
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Trichomonas gallinae in domestic pigeons (Columba livia domestica) in subtropical southern China

Abstract: Domestic pigeon (Columba livia domestica) as the main host of Trichomonas gallinae plays an important role in the spread of T. gallinae, but limited information about the prevalence of T. gallinae in domestic pigeons in China is available. In the present investigation, a total of 319 domestic pigeons on seven commercial farms in Guangdong Province, Southern China were examined microscopically in freshly prepared wet mount between July 2009 and January 2010. T. gallinae was observed in 108 out of 319 pigeons, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…To understand the factors leading to this rise and fall in T. gallinae positivity rates, investigations, such as those conducted by Alasadiy et al (2022) , have suggested that artificially reared pigeons exhibit higher positivity rates than wild pigeons, a phenomenon potentially attributed to the rearing environment. In addition, Qiu et al (2012) found rearing environments with high management standards to have lower T. gallinae positivity rates, while those with poor management practices exhibited high positivity rates. These findings underscored the importance of appropriate management practices and environments in controlling T. gallinae infections.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To understand the factors leading to this rise and fall in T. gallinae positivity rates, investigations, such as those conducted by Alasadiy et al (2022) , have suggested that artificially reared pigeons exhibit higher positivity rates than wild pigeons, a phenomenon potentially attributed to the rearing environment. In addition, Qiu et al (2012) found rearing environments with high management standards to have lower T. gallinae positivity rates, while those with poor management practices exhibited high positivity rates. These findings underscored the importance of appropriate management practices and environments in controlling T. gallinae infections.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, as management practices and rearing conditions improved and the environment changed, the positivity rate of T. gallinae decreased. In Guangdong Province, China, T. gallinae infection rates in meat pigeons have been reported since 2009, with a positivity rate of 33.9% in 2009 ( Qiu et al, 2012 ), 36.7% in 2017 ( Qiu et al, 2017 ), and 38.9% in 2020, and a recent publication in 2022 reported a decrease in the T. gallinae positivity rate to 26.6% ( Cai et al, 2022 ). These findings were consistent with the overall global analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…There is no intermediate host,and the life cycle is simple and direct . The domestic pigeon, Columba livia, is the main host of this parasite (Qiu et al, 2012).Additionally susceptible are domestic and wild turkeys, hens, and raptors (such as hawks and golden eagles) (Bulbul et al, 2018). It typically inhabits various bird species upper gastrointestinal tract, particularly Columbiformes (pigeons and doves) (Seddiek et al, 2014).…”
Section: The Confirmatory Diagnosis and Therapeutic Management Of Can...mentioning
confidence: 99%